"n Verruimde invalshoek tot die verlede? Die sosiaal-wetenskaplike benadering tot die Nuwe Testament - Joubert, S. J. (Hervormde teologiese studies, 1991)
A broadened perspective to the past? The social scientific approach to the New Testament This paper focuses on the possibilities that the social scientific approach holds out for the understanding of the New Testament. A review of the contributions of the sociological and the cultural anthropological approaches to the New Testament is undertaken before the social-scientific approach as a whole is evaluated. The use of social-scientific models, in particular, in the construction of the possible social contexts of the New Testament documents, is evaluated in terms of the ability of these contexts to establish ‘new’ systems of meaning.